INDICATORS OF SHORT-TERM BUSINESS STATISTICS IN THE CONTEXT OF THE RUSSIAN CONSTRUCTION INDUSTRY - Olga V. Ledneva (Статистика и экономика, 2016)
A Construction industry is of great interestto business, as its development is ahead ofeconomic development in general. Drop-downor upward trend indicators in the constructionsector dynamics, starts a few blocks earlier thanin other industries. Starting a prolonged slump inthe construction industry can serve as a signalto other industries that need to reduce the paceof investment and to create a reserve of cash in the run-up to the crisis.Construction is one of the branches of the short-term business statistics, which in turn is one of the most important economic statistics,distinguishes from the ofﬁcial statistics by itsdynamism and efﬁciency. The accuracy of the published information is reduced slightly, which can’t be said about the availability, especially forRussian business.